Constructing Usable Documentation: A Study of Communicative Practices and the Early Uses of Mainframe Computing in Industry - Zachry, Mark (Journal of Technical Writing and Communication, 2001)
This study suggests that documentation is a complex technical communication genre, encompassing all the texts that mediate between complex human activities and computer processes. Drawing on a historical study, it demonstrates that the varied forms given to documentation have a long history, extending back at least to the early days of commercial mainframe computing. The data suggest that (1) early forms of documentation were borrowed from existing genres, and (2) official and unofficial documentation existed concurrently, despite efforts to consolidate these divergent texts. The study thus provides a glimpse into the early experimental nature of documentation as writers struggled to find a meaningful way to communicate information about their organization's developing computer technology.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC9jOHRmLXRiYXYtZmg4dS11dTlr